2011
DOI: 10.1016/j.jde.2010.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The Nehari manifold for a Kirchhoff type problem involving sign-changing weight functions

Abstract: This paper examines a class of Kirchhoff type equations that involve sign-changing weight functions. Using Nehari manifold and fibering map, the existence of multiple positive solutions is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
208
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(210 citation statements)
references
References 28 publications
(32 reference statements)
1
208
0
1
Order By: Relevance
“…Furthermore, by means of the tool of Nehari manifold, Zhang et al [36] established the existence theorem of ground states for generalized Choquard equation when the nonlinear term is concave-convex. On the other hand, there are a great deal of results on the existence of elliptic boundary value problems with sign-changing weights [37][38][39][40][41][42][43][44][45]. We should point out that Hsu and Lin [38] showed the existence of positive solutions for elliptic equations with concave-convex nonlinearities and sign-changing weights.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, by means of the tool of Nehari manifold, Zhang et al [36] established the existence theorem of ground states for generalized Choquard equation when the nonlinear term is concave-convex. On the other hand, there are a great deal of results on the existence of elliptic boundary value problems with sign-changing weights [37][38][39][40][41][42][43][44][45]. We should point out that Hsu and Lin [38] showed the existence of positive solutions for elliptic equations with concave-convex nonlinearities and sign-changing weights.…”
Section: Introductionmentioning
confidence: 97%
“…In view of the same method, Chen and Wu [41] obtained the existence of positive solutions for a class of critical semilinear problem. Chen et al [42] established multiplicity .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, positive solutions could be obtained in [2]- [4]. Especially, Chen et al [5] [6], Mao and Luan [7], found sign-changing solutions. As for in nitely many solutions, we refer readers to [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main approach of this paper is the method of Nehari manifold, which was first introduced by Nehari in [31,32], and the method turned out to be very useful in critical point theory (see, e.g., [1,2,10,11,14,15,25,37,38,40,41]) and eventually came to bear his name.…”
Section: Introductionmentioning
confidence: 99%